2012
DOI: 10.1590/s0102-311x2012000600016
|View full text |Cite
|
Sign up to set email alerts
|

Excesso de peso em crianças e adolescentes no Estado de Pernambuco, Brasil: prevalência e determinantes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
66

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 29 publications
4
20
0
66
Order By: Relevance
“…[29][30] The same trend was observed in Pernambuco, where excess weight was significantly higher among children and adolescents from families with a higher income and a better socioeconomic level. 25,31 In the South of the country, in Santa Catarina, the results found in a study of students enrolled in the public and private networks were similar to our research, as a significant association was identified between excess weight and income. 32 Although physical exercise was not associated with overweight in this study, research shows that a higher family income can provide greater access to consumption goods that stimulate sedentariness, like the computer.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[29][30] The same trend was observed in Pernambuco, where excess weight was significantly higher among children and adolescents from families with a higher income and a better socioeconomic level. 25,31 In the South of the country, in Santa Catarina, the results found in a study of students enrolled in the public and private networks were similar to our research, as a significant association was identified between excess weight and income. 32 Although physical exercise was not associated with overweight in this study, research shows that a higher family income can provide greater access to consumption goods that stimulate sedentariness, like the computer.…”
Section: Discussionsupporting
confidence: 88%
“…24 In Pernambuco, in a study involving children and adolescents, using the information available in the Pesquisa Estadual de Saúde e Nutrição (PESN) [State Research of Health and Nutrition] as the data source, in 2006, the prevalence rate of overweight observed was 13.3%. 25 In addition, in a multicenter research that assessed the nutritional status of school-aged children from the Northeast and Southeast of Brazil identified a prevalence rate of 9.5% of overweight. 26 Despite the variations in the prevalence levels of overweight and obesity in the studies indicated, the magnitude of the problems among the school-aged children in our study is clear, as the prevalence of excess weight found is high and demonstrates the need for education and health professionals, families and governments in general to pay attention.…”
Section: Discussionmentioning
confidence: 99%
“…Estes envolveram a faixa etária de dois anos (ABRANTES; LAMOUNIER; COLOSIMO, 2003) a vinte anos de idade (GRIZ et al, 2010;PETRIBU et al, 2011) Griz et al (2010) 6,7% * * 3,7% * * 10,4% * * Leal et al (2012) 9,5% * * 3,8% * * 13,3% * * Mendonça et al (2010) 9,3% * * 4,5% * * 13,8% * * Nunes, Figueiroa e Alves (2007) 18,3% * * 6,8% * * 25,1% * * Oliveira, Cerqueira e Oliveira (2003) 9,3% * * 4,4% * * 13,7% * * Petribú et al (2011) 19% 16,4% 20,6% 5,5% 6,2% 5,1% 24,5% 22,6% 25,7% Silva (2011) 12,9% 13,0% 12,8% 12,9% 14,4% 11,4% 25,8% 27,4% 24,2% Silva, Balaban e Motta (2005) 14,5% * * 8,3% * * 22,8% * * Tassitano et al (2009) 11,5% 11,5% 11,5% 2,4% 1,9% 2,8% 13,9% 13,4% 14,3% Baruki et al (2006) 6,2% Corso et al (2012) 15,4% 15,4% 15,4% 6,1% 6,1% 6,1% 21,5% 21,5% 21,5% Cureau et al (2012) 19,6% * * 4,2% * * 23,8% 32,5% 15,1%…”
Section: Artigosunclassified
“…This nutritional profile has been related to various determinants, especially those related to lifestyle, such as sedentary lifestyle (mainly due to time spent before the TV and/or the computer, to the detriment of the regular practice of physical exercise) and inadequate eating habits (especially the high consumption of manufactured foodstuffs and fast foods) 36 . These habits are at times influenced by the family atmosphere, where they should be regarded as problematic, so that healthier attitudes may be adopted with a view to changing the lifestyle.…”
Section: Resultsmentioning
confidence: 99%